Guidelines for investigating process safety incidents (Wiley, 2019)
"This book provides a comprehensive treatment of investing chemical processing incidents. It presents on-the-job information, techniques, and examples that support successful investigations. Issues related to identification and classification of incidents (including near misses), notifications and initial response, assignment of an investigation team, preservation and control of an incident scene, collecting and documenting evidence, interviewing witnesses, determining what happened, identifying root causes, developing recommendations, effectively implementing recommendation, communicating investigation findings, and improving the investigation process are addressed in the third edition. While the focus of the book is investigating process safety incidents the methodologies, tools, and techniques described can also be applied when investigating other types of events such as reliability, quality, occupational health, and safety incidents"--